Neuroanatomical disposition, natural development, and training-induced plasticity of the human auditory system from childhood to adulthood: a 12-year study in musicians and nonmusicians - Schneider, Peter; Engelmann, Dorte; Groß, Christine; Bernhofs, Valdis; Hofmann, Elke; Christiner, Markus; Benner, Jan; Bücher, Steffen; Ludwig, Alexander; Serrallach, Bettina L.; Zeidler, Bettina M.; Turker, Sabrina; et al. (The journal of neuroscience, 2023)
Auditory perception is fundamental to human development and communication. However, no long-term studies have been performed on the plasticity of the auditory system as a function of musical training from childhood to adulthood. The long-term interplay between developmental and training-induced neuroplasticity of auditory processing is still unknown. We present results from AMseL (Audio and Neuroplasticity of Musical Learning), the first longitudinal study on the development of the human auditory system from primary school age until late adolescence. This 12-year project combined neurologic and behavioral methods including structural magnetic resonance imaging (MRI), magnetoencephalography (MEG), and auditory tests. A cohort of 112 typically developing participants (51 male, 61 female), classified as “musicians” (n = 66) and “nonmusicians” (n = 46), was tested at five measurement timepoints. We found substantial, stable differences in the morphology of auditory cortex (AC) between musicians and nonmusicians even at the earliest ages, suggesting that musical aptitude is manifested in macroscopic neuroanatomical characteristics. Maturational plasticity led to a continuous increase in white matter myelination and systematic changes of the auditory evoked P1-N1-P2 complex (decreasing latencies, synchronization effects between hemispheres, and amplitude changes) regardless of musical expertise. Musicians showed substantial training-related changes at the neurofunctional level, in particular more synchronized P1 responses and bilaterally larger P2 amplitudes. Musical training had a positive influence on elementary auditory perception (frequency, tone duration, onset ramp) and pattern recognition (rhythm, subjective pitch). The observed interplay between “nature” (stable biological dispositions and natural maturation) and “nurture” (learning-induced plasticity) is integrated into a novel neurodevelopmental model of the human auditory system. - Significance Statement We present results from AMseL (Audio and Neuroplasticity of Musical Learning), a 12-year longitudinal study on the development of the human auditory system from childhood to adulthood that combined structural magnetic resonance imaging (MRI), magnetoencephalography (MEG), and auditory discrimination and pattern recognition tests. A total of 66 musicians and 46 nonmusicians were tested at five timepoints. Substantial, stable differences in the morphology of auditory cortex (AC) were found between the two groups even at the earliest ages, suggesting that musical aptitude is manifested in macroscopic neuroanatomical characteristics. We also observed neuroplastic and perceptual changes with age and musical practice. This interplay between “nature” (stable biological dispositions and natural maturation) and “nurture” (learning-induced plasticity) is integrated into a novel neurodevelopmental model of the human auditory system.
Zuerst veröffentlicht: 21. August 2023
Gesehen am 18.06.2024